2022
DOI: 10.1021/acs.joc.2c00281
|View full text |Cite
|
Sign up to set email alerts
|

Borinic Acid Catalyzed Regioselective N-Alkylation of Azoles

Abstract: A method for regioselective N-alkylation of ambident, azole-type heterocycles with alkene or epoxide electrophiles is described. In the presence of diphenylborinic acid (Ph2BOH) and an amine cocatalyst, heterocyclic nucleophiles such as 1,2,3- and 1,2,4-triazoles, substituted tetrazoles, and purine are activated toward selective N-functionalization. The scope of electrophilic partners includes enones, 2-vinylpyridine, phenyl vinyl sulfone, a dehydroalanine derivative, and epoxides. Mechanistic studies, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The results obtained without boronic acid are provided in each case to illustrate the effect of the co-catalyst. Benzotriazole and 1,2,3-triazole favored the N1-allylated product, whereas 1,2,3-triazolo­[4,5- b ]­pyridine underwent allylation at N3, consistent with our previous work . Although 4-substituted 1,2,3-triazoles resulted in mixtures of isomers (products 3d and 3e / 3e′ ), the effect of the boronic acid co-catalyst in promoting “contrasteric” N3-allylation is noteworthy; in the absence of a catalyst, the N3-allylated product was the minor component.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained without boronic acid are provided in each case to illustrate the effect of the co-catalyst. Benzotriazole and 1,2,3-triazole favored the N1-allylated product, whereas 1,2,3-triazolo­[4,5- b ]­pyridine underwent allylation at N3, consistent with our previous work . Although 4-substituted 1,2,3-triazoles resulted in mixtures of isomers (products 3d and 3e / 3e′ ), the effect of the boronic acid co-catalyst in promoting “contrasteric” N3-allylation is noteworthy; in the absence of a catalyst, the N3-allylated product was the minor component.…”
supporting
confidence: 89%
“…Our group has shown that diarylborinic acid catalysts (Ar 2 BOH) activate azole-type heterocycles toward regioselective functionalizations with epoxides and electron-deficient alkenes (Scheme ). The proposed mechanism involves a catalyst binding to both the nucleophile and the electrophile, with the mode of N-coordination to the azole influencing the regiochemical outcome. We sought to build on this result by exploring synergistic organoboron/transition metal catalysis, with the aim of diversifying the types of heterocycle functionalization that could be achieved.…”
mentioning
confidence: 99%
“…Recently, Taylor and co-workers reported the ability of diphenylborinic acid in tandem with simple amine cocatalysts to promote the regioselective N-alkylation of a variety of azole heterocycles (Scheme 46). 150 Interestingly, though the reaction proceeded well with several classes of electrophilic alkenes and epoxides, the use of other electronically similar electrophilic alkenes abolished regioselectivity. Though the origins of the loss of selectivity are unclear, these data indicate that the precise nature of the electrophile can have a profound impact.…”
Section: ■ Alkylationmentioning
confidence: 99%
“…5 Most recently, Taylor and co-workers reported boronic acid-catalyzed conjugated addition of 1,2,4-triazoles to Michael acceptors to afford N 1 -alkylated products with high regioselectivities (Scheme 1b(3)). 6 Although several approaches to N 1 -substituted 1,2,4-triazoles via effective annulation have been documented, 1 c the development of efficient methods of regioselective N 1 -alkylation of 1,2,4-triazoles is still highly appealing.…”
Section: Introductionmentioning
confidence: 99%